Analisis Faktor-Faktor yang Mempengaruhi Perilaku Moralitas Mahasiswa Akuntansi di Kota Batam - Noviyani, Noviyani; Natalia, Erni Yanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research was to evaluate, test, and analyze how influential the accounting profession's code of ethics, intellectual quotient, emotional intelligence, and spiritual intelligence have on moral behavior. Universitas International Batam and Universitas Universal are the locations in this research, specifically in the Accounting study program. The sampling technique used in this study was purposive sampling using the slovin formula so that the sample obtained was 313 respondents. The sample that was used as the subject of this study was accounting students class of 2021. The total population in this study was 1,405 students. The results of the T test study obtained the professional code of ethics variable for the accounting profession partially affecting morality behavior, the intellectual quotient variable partially influencing morality behavior, emotional intelligence variable partially influencing morality behavior, spiritual intelligence variable partially influencing morality behavior. The results of the F test study obtained the accounting profession's code of ethics, intellectual intelligence, emotional intelligence, and spiritual intelligence with a significant value of 0.000 <0.005, which means that the accounting profession's code of ethics, intellectual quotient, emotional intelligence, and spiritual intelligence simultaneously affect moral behavior. Keywords : Code of ethics for the accounting profession, Intellectual Quotient,Emotional Intelligence, Spiritual Intelligence